Is Elective Soft Tissue Hand Surgery Associated with Periprosthetic Joint Infection after Total Joint Arthroplasty?. Issue 10 (October 2019) - Li, Kevin; Jiang, Sam Y.; Burn, Matthew B.; Kamal, Robin N.
Abstract: Background: Although current guidelines do not recommend the routine use of surgical antibiotic prophylaxis to reduce the risk of surgical site infection following clean, soft tissue hand surgery, antibiotics are nevertheless often used in patients with an existing joint prosthesis to prevent periprosthetic joint infection (PJI), despite little data to support this practice. Questions/purposes: (1) Is clean, soft tissue hand surgery after THA or TKA associated with PJI risk? (2) Does surgical antibiotic prophylaxis before hand surgery decrease PJI risk in patients with recent THA or TKA? Methods: We assessed all patients who underwent THA or TKA between January 2007 and December 2015 by retrospective analysis of the IBM® MarketScan® Databases, which provide a longitudinal view of all healthcare services used by a nationwide sample of millions of patients under commercial and supplemental Medicare insurance coverage—particularly advantageous given the relatively low frequency of hand surgery after THA/TKA and of subsequent PJI. The initial search yielded 940, 861 patients, from which 509, 896 were excluded for not meeting continuous enrollment criteria, having a diagnosis of PJI before the observation period, or having another arthroplasty procedure before or during the observation period; the final study cohort consisted of 430, 965 patients of which 147, 398 underwent THA and 283, 567 underwent TKA. In the treated cohort, 8489 patients underwent carpal tunnel release, trigger finger release, ganglion or retinacular cyst excision, de Quervain's release, or soft-tissue mass excision within 2 years of THA or TKA. The control cohort was comprised of 422, 476 patients who underwent THA or TKA but did not have subsequent hand surgery. The primary outcome was diagnosis or surgical management of a PJI within 90 days of the index hand surgery for the treated cohort, or within a randomly assigned 90-day observation period for each patient in the control group. Propensity score matching was used to match treated and control cohorts by patient and treatment characteristics and previously-reported risk factors for PJI. Logistic regression before and after propensity score matching was used to assess the association of hand surgery with PJI risk and the association of surgical antibiotic prophylaxis before hand surgery with PJI risk in the treated cohort. Other possible PJI risk factors were also explored in multivariable logistic regression. Statistical significance was assessed at α = 0.01. Results: Hand surgery was not associated with PJI risk after propensity score matching of treated and control cohorts (OR, 1.39; 99% CI, 0.60–3.22; p = 0.310). Among patients who underwent hand surgery after arthroplasty, surgical antibiotic prophylaxis before hand surgery was not associated with decreased PJI risk (OR 0.42; 99% CI, 0.03–6.08; p = 0.400). Conclusions: Clean, soft-tissue hand surgery was not found to be associated with PJI risk in patients who had undergone primary THA or TKA within 2 years before their hand procedure. While the effect of PJIs can be devastating, we do not find increased risk of infection with hand surgery nor data supporting routine use of surgical antibiotic prophylaxis in this setting. Level of Evidence: Level III, therapeutic study.